Performa Termal dan Hidrolik Aliran Udara Melalui Vortex Generator Berlubang Tipe Concave Rectangular Winglet di dalam Saluran Persegiempat: Studi Eksperimen - Syaiful, Syaiful; Syarif, Ahmadi; Yunianto, Bambang; Sinaga, Nazaruddin (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
Fin and tube heat exchangers use gas as a cooling/heating medium on the fin side. The low thermal conductivity of gases results in high thermal resistance, which results in a low rate of heat transfer. Therefore, the researchers sought to reduce thermal resistance on the fin side. This study aims to increase heat transfer by reducing thermal resistance using a longitudinal vortex generator. However, the use of vortex generators will increase the pressure drop. Perforated vortex generators were investigated in this study to overcome this problem. Concave rectangular winglet vortex generator at an angle of attack of 30Â° with variations of without hole, one, two, and three holes were studied. In this experiment, the number of pairs of vortex generators was varied from one to three pairs. A plate on which the vortex generator is mounted is heated at a heat rate of 35 W. Air enters the channel through the straightener at variations in the velocity of 0.4 m/s to 2 m/s at intervals of 0.2 m/s. The results showed that the value of the convection heat transfer coefficient for the use of perforated concave rectangular winglet vortex generators was 85.4% higher than the baseline. This value is 13.7% higher than the use of perforated rectangular winglet vortex generators. Whereas the value of pressure drop for the use of perforated concave rectangular winglet vortex generators is five times higher than that of the baseline. This value is 104.9% higher than the use of perforated rectangular winglet vortex generators.